ANALYSIS OF THEORETICAL APPROACHES TO THE STUDY OF GLOBALIZATION AND NATIONAL IDENTITY (BASED ON THE WORKS OF UZBEK SCHOLARS) - Toshmurodov, Husanjon Erkinovich (Oriental Journal of History, Politics and Law, 2026)
This thesis analyzes the theoretical approaches of Uzbek scholars to the study of the problem of national identity under the conditions of globalization processes. It provides a comparative analysis of the works of S. Otamurodov, B. Umarov, Sh. Madayeva, Z. Odinayeva, M. Ravshanova, X. Kadirova, A. Xursandov, X. Soqiyev, and D. Kalandarova, which are devoted to the political-philosophical and socio-economic analysis of globalization, as well as to the anthropological, axiological, comparative-philosophical, and socio-political aspects of national identity. The research findings show that in Uzbek scholarly literature, national identity under conditions of globalization is interpreted not as a static phenomenon, but as a multilayered, dynamic phenomenon shaped by the influence of various socio-cultural factors.